Исследования палеолитических памятников на юге Черкасской области в 2008 г. - Степанчук, В.Н.; Сиволап, М.П.; Матвиишина, Ж.Н.; Кармазиненко, С.П. (Археологічні дослідження в Україні, 2009)
In July 2008 in the west of Cherkasy Oblast in the basin of the Southern Buh River the Palaeolithic sites Nechayeve 3, Maslove 5 and Maslove 5в were studied. For the first time in the region the existence of the Middle Palaeolithic artefacts sometimes with animal bones and malacofauna is reliably veri fied in stratified context in the layers dated from 100 to 30 thousand BP. Flint artifacts in the Middle Pleistocene layers dated at least 300 thousand BP have been discovered here.